Response of estuarine free-living nematode assemblages to organic enrichment: an experimental approach - Kandratavicius, Noelia (2018)
Organic enrichment, especially from anthropogenic sources, is one of the currentthreats to coastal marine biodiversity. Organic enrichment occurs mainly in sheltered soft bottoms,characterized by fine sediments, and results in multiple changes in the benthic habitat, includinghypoxia and an increased concentration of compounds that are toxic to marine invertebrates. Wereport on the results of a microcosm-based experiment (duration = 30 d), quantifying the effects oforganic enrichment on taxonomic and functional diversity of nematode assemblages from anopen/closed coastal lagoon of South America (Rocha Lagoon, Uruguay). In open/closed lagoons,the input of organic matter becomes a major disturbance due the limitation in water renewal. Inour experiment, enrichment led to reductions in abundance, richness and trophic diversity of thenematode assemblage. Rapid reductions in total abundance (after 4 d) were registered, while richnessdecreased only towards the end of the experiment (~30 d). Trophic changes were characterizedby loss of predators/omnivores and dominance of selective deposit-feeders and epigrowthfeeders.By contrast, we did not find any selective effect of enrichment associated with life historytraits (e.g. maturity index). Overall, these findings have 2 important implications for the conservationand monitoring of the health of coastal lagoons: first, monitoring of nematode assemblages atthe genus level is sufficient to detect enrichment effects; second, an index of trophic diversitywould be a good indicator of the effects of enrichment on natural communities.